TRENDS IN THE DYNAMICS OF MUNICIPALITIES’ OWN REVENUES IN BULGARIA - Ivanova, Diyana (E-Journal VFU, 2025)
In order for municipalities to achieve a good financial position, it is crucial for them to be financially independent, which in turn depends on the revenue section of municipal budgets and, more specifically, on municipalities’ own revenues. A good revenue base is a prerequisite for successfully financing the local spending responsibilities assigned to them and for achieving the set operational and strategic goals. The topic of municipalities’ own revenues in Bulgaria is increasingly relevant in the context of their decreasing financial independence and increasing dependence on the state budget. The aim of this paper is to study municipalities’ own revenues by tracking their dynamics and highlighting the trends in their development.